Justice on Trial: How Artificial Intelligence is Reshaping Judicial Decision-Making - Andriati, Syarifah Lisa; Rizki, Inneke Kiki; Malian, Ain Najwa Binti Mohd (Journal of Indonesian Legal Studies, 2024)
The integration of Artificial Intelligence (AI) into judicial decision-making processes is reshaping the administration of justice, offering new possibilities for efficiency and consistency while raising critical concerns about fairness and judicial discretion. This research explores the use of AI to support judges in their decision-making processes, focusing on the balance between technological assistance and the human consideration of justice. Additionally, it examines the regulatory frameworks that enable and govern AI’s role in the judiciary. Employing a normative juridical research methodology and secondary data from literature reviews, this study finds that AI systems can only assist judges by providing recommendations rather than replacing their judgment. Algorithms and mathematical models cannot fully account for the complex, qualitative factors inherent in the pursuit of justice, such as moral considerations, empathy, and societal context. Currently, AI usage in judicial processes is not explicitly regulated; however, it may be justified under Article 1 Point 8 of Indonesia’s ITE Law, which recognizes electronic agents controlled by humans to achieve specified objectives. The research underscores that AI’s potential lies in its capacity to complement human judges by enhancing efficiency and reducing bias in routine tasks, while ultimate decision-making must remain a human responsibility. This study concludes that the responsible use of AI, guided by clear legal and ethical frameworks, can ensure that technological advancements in the judiciary uphold the principles of justice and human dignity.